A diversidade sonora na flauta transversal: representações conceituais e acústicas, aplicações pedagógicas e criativas - Rodrigo Manoel Frade (2022)
The flute is a musical instrument explored in different repertoires and musical styles, presenting great sound diversity and a range of creative-expressive possibilities. In this work, we approach the different sonorities of the flute, especially those explored in the contemporary repertoire. Its particularities are analyzed from the points of view of acoustics and performance, in dialogue with the perceptual criteria proposed by Pierre Schaeffer. These sounds were explored by young composers, participants of the Festival Escuta Aqui!, who composed pieces premiered by the author of this work. Excerpts from these pieces exemplify the flute sounds in their association with Schaefferian type-morphological criteria. We developed an interactive tool in Max that, relating audio descriptors to such criteria, provides musicians with real-time visual feedback. The descriptors chosen were attack profile, dynamic envelope, number of partials representing 50 and 80% of the total energy of the sound, presence of iterative and fine grains, presence of allures, fundamental frequency (if any), spectral centroid, intrinsic dissonance, spectral distribution. The instrumental practice with the visual support of these descriptors allowed a better understanding of certain aspects of the different sounds explored by the contemporary repertoire, in addition to providing comparisons between different performance strategies and the results obtained. We presented an experience report with an undergraduate music group where it was possible to apply our tool in the flutist’s study practice. We also discuss our creations based on exploration of Schaeffer's perceptual criteria and the interaction provided by the visual feedback tool. This work represents an important contribution to the understanding of the sound diversity of the flute, a subject treated from different perspectives that are aimed at both flutists and composers.